Molecular detection of piroplasms, Anaplasma, and Ehrlichia species in Kazakhstan - Zeng, Weixin; Kairat, Zhumanov; Awulibieer, Madina; Abylay, Sansyzbay; Serik, Khizat; Yang, Meihua; Wang, Yuanzhi; Hazihan, Wurelihazi (Frontiers in Veterinary Science, 2025)
Tick-borne pathogens (TBPs) are a global public health issue. However, there have been few reports on the prevalence of piroplasms, Anaplasma, and Ehrlichia in Kazakhstan. To understand the distribution of piroplasms, Anaplasma, and Ehrlichia pathogens carried by ticks in Kazakhstan, a total of 10,461 ticks were collected from natural hosts (e.g., cattle, sheep, and horses) in six oblasts in eastern, southern, and western Kazakhstan between 2022 and 2024. After morphological identification, 272 representative ticks were further used for species-level detection and partial genotyping analysis of TBPs. Two Babesia species (Babesia occultans and Babesia caballi), four Theileria species (Theileria orientalis, Theileria equi, Theileria annulata, and Theileria ovis), two Anaplasma species (Anaplasma phagocytophilum and Anaplasma ovis), and three Ehrlichia species were detected. Furthermore, genotype B of B. caballi, genotype 1 (Chitose) of T. orientalis, and genotype A of T. equi were confirmed. For the first time, A. phagocytophilum, three phylogeny-independent Ehrlichia spp., genotype B of B. caballi, and genotype A of T. equi were found in Kazakhstan. These findings expand our understanding of the geographical distribution of piroplasms, Anaplasma, and Ehrlichia in Central Asia.